Precision and coordination parameters of Polish elite cadet fencers - Rokita, A.; Bronikowski, M.; Popowczyk, M.; Cichy, I.; Witkowski M. (Medicina dello Sport, 2014)
Aim. The study aimed at recognizing relationship between selected motor, especially coordination and spatial orientation skills and factors determining place on the National ranking list of 14-16-years-old elite Polish cadet foil fencers were analyzed. Methods. The study was carried on a group of 16 Polish elite fencers aged 14 to 16 years (9 male fencers, 58.7±9.58 kg, 172.4±7.73 cm, 7 female fencers, 54.5±5.50 kg, 166.0±9.14 cm). The study design used three tests: 2 hand test (from Vienna Test System) for precision and time, five-time shuttle run to gates test for spatial orientation, and 2 meter run test for reaction times. Results. The analysis of regression model revealed that the position on the top athlete ranking in cadet fencing was correlated to the level of spatial orientation (â=0.50), hand precision (â=0.64), and chronological age (â=0.56). Conclusion. Fencing is a combat sport requiring parallel development of motor and psychological abilities. Among those coordination, speed of the whole body, as well as reaction time and quick decision making time are the most desirable in terms of quality and thus worth in-depth research. Development of coordination abilities and skills at various phases of the athletic training is likely to contribute to achievement of better results in competitive periods in fencing. These relationships could also be studied in a longitudinal study, which aimed at confirming the strength and importance of the relationship found for the fencers position on the ranking list in senior category.